A large data resource of genomic copy number variation across neurodevelopmental disorders - Zarrei, Mehdi; Burton, Christie L.; Engchuan, Worrawat; Young, Edwin J.; Higginbotham, Edward J.; MacDonald, Jeffrey R.; Trost, Brett; Chan, Ada J. S.; Walker, Susan; Lamoureux, Sylvia; Heung, Tracy; Mojarad, Bahareh A.; et al. (Npj genomic medicine, 2019)
Copy number variations (CNVs) are implicated across many neurodevelopmental disorders (NDDs) and contribute to their shared genetic etiology. Multiple studies have attempted to identify shared etiology among NDDs, but this is the first genome-wide CNV analysis across autism spectrum disorder (ASD), attention deficit hyperactivity disorder (ADHD), schizophrenia (SCZ), and obsessive-compulsive disorder (OCD) at once. Using microarray (Affymetrix CytoScan HD), we genotyped 2,691 subjects diagnosed with an NDD (204 SCZ, 1,838 ASD, 427 ADHD and 222 OCD) and 1,769 family members, mainly parents. We identified rare CNVs, defined as those found in <0.1% of 10,851 population control samples. We found clinically relevant CNVs (broadly defined) in 284 (10.5%) of total subjects, including 22 (10.8%) among subjects with SCZ, 209 (11.4%) with ASD, 40 (9.4%) with ADHD, and 13 (5.6%) with OCD. Among all NDD subjects, we identified 17 (0.63%) with aneuploidies and 115 (4.3%) with known genomic disorder variants. We searched further for genes impacted by different CNVs in multiple disorders. Examples of NDD-associated genes linked across more than one disorder (listed in order of occurrence frequency) are NRXN1 , SEH1L , LDLRAD4 , GNAL , GNG13 , MKRN1 , DCTN2, KNDC1 , PCMTD2 , KIF5A , SYNM , and long non-coding RNAs: AK127244 and PTCHD1-AS . We demonstrated that CNVs impacting the same genes could potentially contribute to the etiology of multiple NDDs. The CNVs identified will serve as a useful resource for both research and diagnostic laboratories for prioritization of variants.